AB0288 The 24-Month Study of Treatment with Monoclonal Antibody To RANKL on Bone Mineral Density and Structural Damage in Patients with Osteoporosis and Rheumatoid Arthritis. (15th July 2016) - Kovalenko, P.; Dydykina, I.; Petrova, E.; Smirnov, A.; Alexeeva, L.; Nasonov, E.
Abstract : Background: Chronic synovitis and RANKL-dependent osteoclastogenesis in rheumatoid arthritis (RA) lead to bone damage, such as local and systemic bone destruction (osteoporosis (OP), erosions and joint space narrowing). RANK-ligand is essential for osteoclast development, activation, and survival. The addition of an anti-RANKL antibody (denosumab) to the traditional scheme of RA treatment is a potentiality to control and prevent joint destruction as well as inhibit systemic osteoporosis. Objectives: The aim is to evaluate the effects of continuous treatment with denosumab on bone mineral density and structural damage in patients with RA and OP. Methods: 27 postmenopausal women (mean age 58, 4±7, 4 years) with RA (mean duration of RA 19, 5±11, 8 years) and OP received subcutaneously denosumab 60 mg every 6 months pro 2 years. According to X-ray 8 (29, 6%) patients had the 2nd, 8 (29, 6%) – the 3rd and 11 (40, 8%) – the 4th stage of RA. 17 patients (62, 9%) continued glucocorticoids (GC). The primary end points were the change from baseline in BMD (by dual energy x-ray absorptiometry at three sites: lumbar spine (L1-L4), hip neck (HN) and distal forearm (DF), the change in Sharp/van der Heijde (SVH) score by X-ray of hands and feet and the change in X-ray morphometric analysis of deformations in vertebrae (Genant method). The change of pain severity in spine was assessed using VAS. The Statistica 6.0 was used. Results: At L1-L4 the significant increase of BMD was noted both at 12- and 24-month point in comparison with baseline: 0, 789±0, 079 g/cm 2 vs 0, 818±0, 077 g/cm 2 (p<0.001) and 0, 789±0, 079 g/cm 2 vs 0, 836±0, 078 g/cm 2 (p<0.001), respectively. The same was noted at DF – the increase of BMD at 12- and then at 24-month: 0, 480±0, 102 g/cm 2 vs 0, 493±0, 095 g/cm 2 (p=0.01) and 0, 480±0, 102 g/cm 2 vs 0, 511±0, 104 g/cm 2 (p<0.001), respectively. At HN it was noted the stabilization in BMD (statistically nonsignificant improvement) at both points. After separation on groups based on GC intake, this trend was also seen at both points in both groups: increase of BMD at L1-L4 and DF, stabilization of BMD at HN. The erosion and total SVH score were increased at 12- and 24-month (p<0.05), while the narrowing score was not changed significantly at both points. The index of vertebral deformations was not changed after 24-month compared with baseline: 0, 79±0, 01 for lumbar site and 0, 76±0, 04 for thoracic site, respectively. At baseline 13 patients had pain in thoracic site of spine, while after the treatment their number significantly decreased (p=0.019) more that 2-fold – 4 (mean VAS 41.1±16.9 and 31.2±8.5 mm, respectively), at lumbar spine pain was also reduced (p=0.09): 15 and 8 patients (44.3± 23.3 and 35.6±14.7 mm, respectively). Conclusions: Throughout the 24 months of therapy with denosumab it was shown the continued increase of BMD at L1-L4 and distal part of forearm - the significant increase was observed both at the first and the following year of therapy regardless of GC intake. At HN it was observed the stabilization of BMD. The erosion and total SVH score were increased, but the narrowing score didn't change after two years of observation. The index of vertebral deformations remained stable. The frequency and severity of pain in spine were decreased. Disclosure of Interest: None declared